The Sleep Hygiene Inventory for Pediatrics: Development and Validation of a New Measure of Sleep in a Sample of Children and Adolescents With Chronic Headache. (November 2017) - Rabner, Jonathan; Kaczynski, Karen J.; Simons, Laura E.; Lebel, Alyssa A.
Sleep plays a pivotal role in children and adolescents with headache. Although several sleep measures exist, no developed measures target the sleep issues common in pediatric patients with headache. The Sleep Hygiene Inventory for Pediatrics (SHIP) was developed for clinical purposes to fulfill this need. The aim of this study was to validate the SHIP for potential research applications in a sample of 1078 children and adolescents (7-17 years) with a primary headache diagnosis. Measure validation included assessments of internal consistency, construct validity, and criterion validity. The SHIP demonstrated strong internal consistency (Cronbach α = 0.84). The SHIP differentiated well between participants for whom sleep was and was not a clinical concern ( P < .001; d =1.65), and was positively correlated with anxiety, depression, and disability. These analyses suggest that the SHIP is a psychometrically strong and valid assessment of sleep habits in pediatric patients with headache.